Popular Biobibliographic Essay (The Evolution of the Genre in RSL Publications) - M. E. Babicheva (Библиосфера, 2022)
The article examines the evolution of the modern genre of recommended bibliographic publications, which is clearly tracked in the publications of the Russian State Library (RSL). The author’s goal is to show how the signs that make the genre popular for modern cultural and educational activities have been formed and consolidated in the process of evolution. The relevance of the research is to identify the opportunities to use recommended bibliographic publications more effectively to promote a book to a reader. The popular biobibliographic essay has become an evolutionary pinnacle for two types of recommended bibliographic products. These are personal indexes, where information about a person is combined with information about literature (publications) plus a detailed review in the genre of «conversations about books». Both types of indexes go back to the list of recommended literature, with the creation of which in the 1920s the recommendation bibliographic activity of the RSL began. In the 1980s, in the RSL there appeared publications, which became the prototype of modern popular biobibliographic essays. The decisive influence on the formation of the genre of popular biobibliographic essay had «perestroika». The recommendation bibliography was actively engaged in navigation in the array of the most popular literature, And in parallel it turned to the little-known and hard-to-access literature. In both cases, new tasks appeared. Some authors had to be selected from the total number, while others, in fact, had to be introduced. A modern essay, accordingly, gives a comprehensive picture of life and work of the person to whom it is dedicated. It creates the image of a person, shows his (her) place in the cultural context, analyzes creativity in general, and characterizes specific book publications.